Is Employment Polarization Informative about Wage Inequality and Is Employment Really Polarizing? - Jennifer Hunt; Ryan Nunn (Institute of Labor Economics (IZA), 2019)
Equating a job with an individual rather than an occupation, we re-examine whether U.S. workers are increasingly concentrated in low and high-wage jobs relative to middle-wage jobs, a phenomenon known as employment polarization. By assigning workers in the CPS to real hourly wage bins with time-invariant thresholds and tracking over time the shares of workers in each, we do find a decline since 1973 in the share of workers earning middle wages. However, we find that a strong increase in the share of workers in the top bin is accompanied by a slight decline in the share in the bottom bin, inconsistent with employment polarization. Turning to occupation-based analysis, we show that the share of employment in low-wage occupations is trending up only from 2002-2012, and that the apparent earlier growth and therefore polarization found in the literature is an artefact of occupation code redefinitions. This new timing rules out the hypothesis that computerization and automation lie behind both rising wage inequality and occupation-based employment polarization in the United States.
Keywords: J31; J62; 330; employment polarization; wage inequality